Prevalence of hypothermia in the first hour of life of premature infants weighing ≤ 1500g - Tamara Soares; Géssica Almeida Pedroza; Márcia Koja Breigeiron; Maria Luzia Chollopetz da Cunha (Universidade Federal do Rio Grande do Sul, 2019)
Abstract Objective: To analyze the prevalence of hypothermia in the first hour of life of preterm infants with birth weight 1,500 g or less. Method: A cross-sectional study performed in a Neonatal Intensive Care Unit. Data obtained from 359 computerized records of premature infants admitted between 2012 and 2016. Descriptive Statistics and Poisson Regression were used. Results: Premature infants (66.9%) presented hypothermia in the first hour of life, with axillary temperature of 36.2ºC (35.7-36.6), associated with: diagnosis of preeclampsia (p = 0.001), small for gestational age (p = 0.029), and the need for chest compression in the delivery room (p = 0.001). In cases of peri-intraventricular hemorrhage grade III (75%) and death (78.9%), there was a prevalence of premature infants with hypothermia in the first hour of life. Conclusion: Hypothermia in the first hour of life was prevalent in preter m infants, being associated with clinical complications. The prevention of hypothermia in the first hour of life is fundamental in the reduction of diseases related to prematurity.